Degreening and Low Temperature Storage to Improve the Quality of Mandarin Orange - Henny Nurpa Anggriani; Sutrisno Sutrisno; Slamet Susanto (The University of Lampung, 2023)
Several citrus species when physiologically ripe are still yellow-green in color, one of which is the Tangerine RGL (Rimau Gerga Lebong) grown in the city of Pagar Alam, South Sumatra. To improve the physical quality of tangerines, RGL can be applied with degreening technology and low-temperature storage. This study aims to examine the effect of degreening and low-temperature storage on physicochemical changes and to determine the optimum method of degreening and low-temperature storage on citrus quality. This study used a completely randomized 2-factor design. The first factor is degreening with 4 levels (0 ppm, 250 ppm, 500 ppm, 750 ppm), and the second factor is storage temperature with 3 temperature levels (10ºC, 20ºC, and room temperature). The results showed degreening increased the CCI value by 3.48-3.82, changing the skin color to uniformly yellow and did not affect the internal quality of the fruit. Treatment with a temperature of 10oC extended the shelf life of the fruit up to 29 days. The combination of 250 ppm ethepon and 10oC effectively suppressed weight loss to maintain the quality of RGL tangerines. Keywords: Degreening, Low-temperature storage, RGL tangerines, Shelf life, Uniform color